THE EFFECT OF THE DISCOVERY LEARNING MODEL ON THE LEARNING OUTCOMES OF GRADE V STUDENTS IN THE INDEPENDENT CURRICULUM - Amalia, Rizqi Laily; Rezania, Vanda (Universitas Muhammadiyah Mataram, 2025)
The DL learning model emphasizes student-centered learning, one of which is to encourage students to find concepts independently through direct learning experiences. This model is believed to improve concept understanding and student learning outcomes, especially at the elementary school level. The purpose of the research is to find out how the DL model affects the learning outcomes of VA class students of SDN Gedang Porong 1 in the independent curriculum. The method applied is preexperimental design with the type of one group pretest-posttest design. Researchers took a population of 28 students in class VA. The research subjects included VA class students who were given DL-based learning treatment. The data collection technique used the initial (pretest) and final (posttest) treatment tests. The sampling technique used saturated sampling technique. The data collection technique applied is the test technique used to find data about student learning outcomes. The research instrument used test sheets for pretest and posttest questions. Data analysis techniques using descriptive statistics using paired sample t-test. The results of the study prove that the average score of students' pre-test reached 75.57, while the average posttest score increased to 93. The results of data analysis with the t-test showed a significant level of <0.001 which is smaller than <0.05, so it can be concluded that there is a significant difference in learning outcomes before and after applying the DL model.